Expressive illocutionary acts and politeness in managerial responses to online hotel reviews - Aleksandra Radovanović (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper explores expressive illocutionary acts in responses to hotel guests' reviews posted on Tripadvisor and aims to compare their occurrences and realizations in 320 managerial responses in English from English and Serbian hotels, with manifestations of linguistic politeness a focus of analysis. Drawing largely on Leech's (2014) framework, it has attempted to determine whether the acts which tend to come in the form of formulaic, routinized expressions occurring in the responses written by hotel representatives with different backgrounds exhibit some differences as a reflection of culture-specific politeness values. The analysis has revealed considerable similarity between the two data sets in the lexico-grammatical realization of expressives and the use of resources for politeness. However, some noteworthy points of dissimilarity have emerged which correlate closely with the differences in cultural value preferences of the two countries in Hofstede et al.'s (2010) dimensions of power distance and of individualism.